Hydroxychloroquine and azithromycin alter the contractility of living porcine heart slices - Wu, Qin; Ross, Abigail J.; Ipek, Tugce; Thompson, Georgina H.; Johnson, Robert D.; Wu, Changhao; Camelliti, Patrizia (Frontiers in Pharmacology, 2023)
The cardiotoxicity risk of hydroxychloroquine (HCQ) and azithromycin (AZM) has been the subject of intensive research triggered by safety concerns in covid-19 patients. HCQ and AZM have been associated with QT interval prolongation and drug-induced arrhythmias, however other cardiotoxicity mechanisms remain largely unexplored. Our group has pioneered the living heart slice preparation, an ex-vivo platform that maintains native cardiac tissue architecture and physiological electrical and contractile properties. Here, we evaluated the cardiotoxic effect of HCQ and AZM applied alone or in combination on cardiac contractility by measuring contractile force and contraction kinetics in heart slices prepared from porcine hearts. Our results show that clinically relevant concentrations of HCQ monotherapy (1-10µM) reduced contractile force and contraction kinetics in porcine slices in a dose-depended manner. However, AZM monotherapy decreased contractile force and contraction kinetics only at higher concentrations (30µM). Combination of HCQ and AZM induced a dose-dependent effect similar to HCQ alone. Furthermore, pre-treating porcine heart slices with the L-type calcium channel agonist Bay K8644 prevented the effect of both drugs, while administration of Bay K8644 after drugs interventions largely reversed the effects, suggesting a mechanism involving inhibition of L-type calcium channels. These findings indicate that HCQ and AZM alter cardiac function beyond QT prolongation with significant contractile dysfunction in intact cardiac tissue. Our porcine heart slices provide a powerful platform to investigate mechanisms of drug cardiotoxicity.